Economic Democracy, Social Dialogue, and Ethical Analysis: Theory and Practice - Chaves, Jorge Arturo (Journal of business ethics, 2002)
The purpose of this article is to present in a summarized form a new approach to the ethical analysis of economic policies and to illustrate its importance with a reference to recent experiences of social dialogue in Costa Rica., A general view of the Latin American scenario is presented, with the belief that some of the main problems there observed call for a type of analysis like the one here proposed. In the second place, a brief characterization of this new ethical analysis is included., Democracy suffers from the existence of asymmetries in social and economic relationships, insofar as the success of political democracy cannot be neither understood nor built up independently from economic democracy. The strengthening of democratic processes in Latin America requires a better understanding and consolidation of the relationship between political democracy and economic democracy. On the other hand, present orientation of globalization makes of the international environment an obstacle to realize democracy at a national level. Hence, two focus of interest arise for the ethical analysis of economics at the macroeconomic level: the study of the ethical conditions of participation for each country in the globalization process, and the realization of an economic democracy within each particular country., After identifying both lines of reflection, this article summarizes the theoretical basis of a proposal for the ethical analysis of economic policy making. This approach attempts to answer the challenges of economic democratization. Centered on the ethical dimension of these processes, and from the point of view of a dialogical ethics, stress is given to those aspects of the process which will guarantee the ethical character of the consequences. This is a methodological approach which tries to discover the ethical values feasible within the economic policies and, at the same time, to go in greater depth in the construction of democratic practices. Rooted in the Latin American regional reality, this academic reflection is just in its beginning and must be considered as complementary to the business ethics analysis already developed in Latin America and Spain., A reference to recent experiences of social dialogue in Costa Rica gives the theoretical presentation a support for the acceptance of its realization in practice.